DEVELOPMENT OF BLOCK 2 MSP1GENE EPITOPE CANDIDATE Plasmodium falciparum BASED ON GENETIC POLYMORPHISMS FOR ENDEMIC AREAS JAYAPURA - MAWARDI (NIM: 21115010), ARSYAM
Malaria is an infectious disease was affected Plasmodium sp. This disease has a high prevalence in the province of Papua with suspected patients about 320.000 in 2015. Previous malaria treatment was done with anti-malarial therapy based on Artemisinin Combination Therapy (ACT). However, this drug therapy was not effective in overcoming malaria because Plasmodium alter the form of abandoned proteins in infected erythrocites. This condition causes the parasites resistant to antimalarial drugs. So, convertion the use of ACT to switch with vaccine therapy was requerement. On the other hand, the vaccine at the blood stage or sporozoite stage currently being developed has not been effective in overcoming malaria. This was due to the high polymorphism of the Plasmodium sp. especially in regions that encode the Plasmodium sp surface protein. Merozoite Surface Protein 1(MSP1) Plasmodium falciparum is a surface protein that plays a role in the invasion process in human erythrocytes through the interaction of Glycophorin A protein receptors and sialic acid in erythrocytes with Reticulocyte Binding Proteins (RBP) and Duffy Adhesion Protein (DAP) ligands in merozoites. Merozoite Surface Protein 1(MSP1) can be targeted to be a specific antigen and predicted epitope area which will be used for the development of diagnostic and malaria vaccine therapy. MSP1 consists of 17 blocks, each block is dimorphic, and has been marked as the K1 and MAD20 alleles. Exceptions are only in block 2, because it has 3 alleles, among others K1, MAD20 and RO33. Genetic polymorphisms and allelic variations implicate the severity of patients infected Plasmodium falciparum. In addition, the polymorphism of MSP1 in Jayapura isolates has not been reported so it is interesting to be further identified and projected as a specific antigen. Therefore, in this study we analyzed the genetic polymorphism as well as mapped the MSP1 antigen on block 2 Plasmodium falciparum. In this reseacrh, clinical samples of selected malaria patients followed the consecutive sampling method, examining malaria parasites with blood preparations on glass objects observed through a microscope. Plasmodium DNA was isolated from the blood of malarial positive patients. The block 2 MSP1 gene was amplified using the PCR method and cloned using the pGEM-T Easy vector and then transformed to TOP'10 E.coli. Positive colonies selection was performed with blue white screening. The presence of target DNA was confirmed by PCR colonies and DNA sequencing methods. Furthermore, DNA sequence analysis was done through alignment and formation of phylogenetic tree using MEGA 6 software and in silico analysis using Immune Epitope Database (IEDB) software to predict the epitope candidate for Plasmodium falciparum. A total of 15 patient samples have been isolated Plasmodium DNA. The PCR amplification results show the target gene size of Ã‚Â± 1049 bp. A total of 20 colonies were obtained from these patients. The results of the MSP1 nucleotide alignment analysis showed that the MSP1 block 2 genes derived from the sample of malarial patients were distributed in three different allele, K1 (8), MAD20 (1), and MSP1_Jayapura (11) alleles . The detected allele most commonly was the MSP1_Jayapura single allele. According to statistical analysis, there was no significant association between sex variables, age, even density of parasitemia against alel variation (Mann Whitney, U> 0.05), while for symptomatic symptoms tested by Chi Square test, it was found that there was significant correlation between symptomatic experienced by malaria sufferer to detectable allelic variation 9 Chi Square; U 0.05). In this study, one group of MSP1 Jayapura has been found that is different from the previously identified allele. The in silico study shows that there was a new epitope antigen candidate from the Jayapura MSP1 allele and predicted to be recognized by antibody with 17 amino acid lengths in amino acid sequence 187 until 203.